Lupus Eritematosus Sistemik pada Pria - Harry Andrean; Raveinal Raveinal (Universitas Baiturrahmah, 2021)
Introduction: Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by presence of nucleus autoantibody and affected multiple organ. Systemic lupus erythematosus is more common in women than men with ratio 2:1 to 15:1. Men with SLE often have a more aggressive clinical course, lead to a poorer prognosis compared with women with SLE. Case Report: A man, 29 years old came to hospital with main complain joint pain increased since 1 week ago, accompanied with red spot on face, trunk, hands, foot, and back, hair loss, swollen leg, mouth ulcer, and fatique. Malar rash and discoid rash were identified from physical examination. From laboratorium, ANA profile was positive for RNP/Sm, Sm, dsDNA, and histone. Skin biopsy showed a lupus discoid. Conclusion: The patient was treated with pulse-dose methylprednisolone for 3 days and showed a good response clinically.